EFICÁCIA DO EXTRATO DE LARANJA VERMELHA CITRUS SINENSIS E O ENGAJAMENTO DOS TUTORES NA REDUÇÃO DO PERCENTUAL DE GORDURA DE CÃES OBESOS - MILLA, EMERSON (2023)
Obesity is the most frequent nutritional disease in dogs, characterized as a low-intensity inflammatory state. The anthocyanins found in red oranges can help to counteract weight gain and to reduce body fat accumulation through modulation of the inflammatory state and reducing lipogenesis. The aim of this study was to compare the effectiveness of red orange extract and the involvement of owners of 23 overweight dogs in a weight loss program over 90 days. Three experimental groups were formed in which all dogs received the same hypocaloric diet, in addition to supplementation with Citrus sinensis red orange extract (G1, n=9), chromium picolinate (G2, n=7) and a placebo (G3, n=7). =7). On the distribution of the Body Condition Score (BCS) determined at the beginning of the study, of the 23 dogs included in the survey, the following were found: BCS 6 (45.8%); 7 (25%); 8 (8.4%) and 9 (20.8%). During the program, most owners reported not being able to involve other residents in the treatment of their dogs. In the final evaluation, when comparing the BCS between the groups, a significant difference was observed in the reduction of the BCS (p=0.004) between G1 and G3, in addition to a significant decrease in the level of HDL cholesterol in G1 (p=0.02). It is concluded that red orange extract can be an ally in weight loss programs for obese dogs. Many tutors do not identify their animals' overweight and have difficulties in following the recommended therapeutic protocols because they are not able to involve all residents of the residence in the program.